A Statistical analysis on MLM Foods, Inc. - Garces, Mae Margaret (College of Engineering, 2001)
One of the main product line of MLM Foods, Inc. is Lumpia X. This study aims to use the tools and statistical analysis techniques to determine the input factors which affect the rejection rate of the Lumpia X. Input factors include the emulsion or the filling temperature and the drum temperature of the filling machine. It also aims to determine the acceptable range of the input settings to come up with the desired output characteristics. Using Pareto analysis and p-tests, the problem was identified. The problem was that the percent reject is greater than that of the allowable which is 3 percent. Furthermore, the rejection was mainly due to the weight of filling which should be 9.5-10.5 g. Seventy (70) samples of Lumpia X and the accompanying data which includes the temperature of emulsion, drum temperature, weight of filling, length, diameter and thickness of wrapper were gathered and recorded. Upon analysis, the group identified that the factors which may be significant are the (a) machines used, (b) temperature of emulsion and (c) drum temperature. The response variable used is the weight of filling. Design of experiments, which include tests of difference between two means, two factor ANOVA and graphical analysis was used. Results show that the machines used were not important factors that would affect the rejects. The results of the two factor ANOVA test were that the drum temperature is insignificant and the filling temperature is significant. The group investigated the relationship of the temperature filling and the number of rejects and found out that the safest range of filling temperature is [-0.5-1.2] degree celcius. The recommended filling temperature will be able to lessen the rejects and therefore, minimize waste of resources and increase productivity.